An analytical study of thematic roles functioning in Hindi syntax - Premathilaka, H. I. (Faculty of Graduate Studies, University of Kelaniya Sri Lanka, 2022)
Thematic roles attempt to capture similarities and differences in verb meaning that are reflected in argument expression, with emergent generalizations that will contribute to the mapping from semantics to syntax. They belong to the semantics or syntax interface. If there is a verb present, it is usually most directly responsible for the thematic role, while the argument specifies the identity of the participants of the sentence. The objective of the present study is to map the thematic roles of Hindi language to identify the thematic relationship in Hindi syntax. The present study focuses on the conceptualization of semantic roles and their status in theories of grammar and the lexicon in Hindi, as well as on diverse and probably complementary ways of deriving or identifying them based on linguistic data. Particularly attention is given to the question of what kind of thematic roles function in Hindi language. Data were gathered using library surveys and verified by Hindi language native speakers. Data analysis was performed as an analytical study based on syntactic and semantic theories. The present analysis was carried out using thematic roles currently identified by linguists. The key research findings of this paper are based on identifying several features of thematic roles belonging to Hindi language. This paper emphasized that different semantic roles can be assigned to arguments of different lexical semantics.
Keywords: Grammar, Hindi lexicon, Hindi syntax, Semantics, Thematic roles